Pemanfaatan limbah buah-buahan dan sayuran untuk eco-enzyme pada budidaya sayuran dan rempah (Utilization of fruits and vegetable waste for eco-enzyme in vegetable and spice cultivation) - Jumini, J; Erida, Gina; Salim, Agus; Santi, Ira Vika; Juliawati, J; Ichsan, Cut Nur (Buletin Pengabdian, 2023)
Eco-enzyme can solve the problem of waste in households and markets. Eco-enzymes can be a resource for healthy and productive cultivation of vegetables and herbs. Utilization of waste into eco-enzymes can be a new source of income and reduce costs for fertilizers and pesticides for vegetables and herbs. Eco-enzymes can be used for various purposes such as pesticides, liquid fertilizers, growth regulators (ZPT), enzymes that are beneficial for crops and the environment. The results of the analysis of pretest, posttest, and community enthusiasm for processing waste into eco-enzyme are very strong, which can be seen from the answers given by the participants after participating in the training on making eco-enzyme. Previously, in the pretest test, it could be concluded that the peoples in Lubuk Batee Village generally did not know how to make eco-enzyme and its application. Posttest after the implementation of making Eco-enzyme, the results of the response analysis from the two partners showed a significant increase in knowledge and skills in both community groups and this continued to increase after they saw the results of eco-enzyme application on crops. The introduction of eco-enzyme production in two community groups in Lubuk Batee Village, Ingin Jaya Subdistrict, Aceh Besar District has increased the knowledge and skills of partners to process waste into useful products and can reduce waste and its side effects on the environment. Eco-enzyme can also be made into various other products that are beneficial to society.